Biomass Volume Estimation and Valorization for Energy 2017
DOI: 10.5772/66334
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Accidents During Marine Transport of Wood Pellets Due to Off-Gassing: Experiences from Denmark

Abstract: The atmosphere in unventilated wood pellet storage confinements, such as the cargo hold of marine vessels transporting pellets in solid bulk, can be severely oxygen deficient and contain deadly concentrations of harmful gasses, of which the most feared is the poisonous and odour-less carbon monoxide. The hazard has been known for over a decade and has been responsible for many accidents. We examine three fatal accidents on marine vessels in or near Danish waters and argue that they share strikingly similar aet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…The vessel departed from Riga (Latvia). It was loaded with 2600 tons of wood pellets destined for the Amagervaerket power plant, owned by Wattenfall, which had recently converted one of its coal blocks to solid biomass [19]. It was reported that two crew members were missing on the ship and were later found dead at the bottom of the stairwell leading to the bow compartment.…”
Section: Accident Involving Lignocellulosic Biomass Storagementioning
confidence: 99%
See 1 more Smart Citation
“…The vessel departed from Riga (Latvia). It was loaded with 2600 tons of wood pellets destined for the Amagervaerket power plant, owned by Wattenfall, which had recently converted one of its coal blocks to solid biomass [19]. It was reported that two crew members were missing on the ship and were later found dead at the bottom of the stairwell leading to the bow compartment.…”
Section: Accident Involving Lignocellulosic Biomass Storagementioning
confidence: 99%
“…During the investigation, it was identified in the wood pellet sample that the concentration of CO in the environment was above 150 ppm, information that, together with the autopsies, confirmed death by CO poisoning, indicating levels of COHb saturation in the blood at 52% and 60% for each of the crew members. The inhalation occurred due to a gap in the door's opening, through which gases traveled from the hold to the bow [19].…”
Section: Accident Involving Lignocellulosic Biomass Storagementioning
confidence: 99%
“…Since oxygen is consumed in the autooxidation processes, its concentration decreases with the incubation time [25]. Along with the presence of CO, this is another factor that poses a threat to the lives of people staying in poorly ventilated rooms and cargo bays where wood pellets are stored [20,43]. The atmosphere is regarded as poor in oxygen when the O 2 concentration is below 19.5% v/v, but a person's ability to judge the situation and to breathe does not worsen until it drops below 16% v/v.…”
Section: Gas Concentration Changesmentioning
confidence: 99%
“…Combined with poor ventilation, the off-gassing lowers the air quality inside and seriously threatens human health (and even life), especially with high concentrations of CO. Numerous cases of fatal poisonings of people in warehouses and ships carrying wood pellets have been documented, which makes the presence of efficient ventilation crucial [20,21]. Pellet off-gassing in storage is caused by autooxidation of lipophilic compounds in biomass, especially unsaturated fats and free fatty acids (e.g., linoleic acid) and resin acids.…”
Section: Introductionmentioning
confidence: 99%